"My God! Why Was I Born?": Illegitimacy, Emotion, and Family in Nineteenth-century France. (October 2018) - Foley, Susan
Unpublished documents by Léon Laurent-Pichat (1823–1886), republican activist and Life Senator, record his experience of being born illegitimate, finding his mother in adulthood, and becoming part of her family. Such accounts are extremely rare. This case study uses those writings to elucidate the emotional impact of illegitimacy on both child and family. It also questions how far the legal and social exclusion of illegitimate children from the conjugal family was reflected in family practice. This case demonstrates that bourgeois families were sometimes less intransigent and more accepting of such children than legal strictures or social prescriptions might suggest.